Secondary glaucoma associated with aphakia following complicated surgery for senile cataract – a review - Gontarz, Katarzyna; Dorecka, Mariola; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Aphakia is an independent risk factor for the development of secondary glaucoma. The literature on this type of glaucoma focuses mainly on pediatric patients, less often adults. The aim of the work is to present the current knowledge on the epidemiology, causes of development and possible treatment of secondary glaucoma in adult aphakic patients after cataract surgery. According to the literature, in the years 1970-1980, glaucoma in aphakic eyes accounted for 37.7% of cases of secondary glaucoma in the population of adults and children, and at the beginning of the 21st century this percentage decreased to 11%. Nevertheless, secondary glaucoma in aphakic eyes is diagnosed in 17.7% of cases. Secondary glaucoma in aphakia is characterized by unclear etiopathogenesis, and often diagnostic and therapeutic difficulties. The most common pathomechanisms of this type of glaucoma include: peripheral anterior synechiae, pupillary block, the presence of a loose vitreous in an anterior chamber and an angle region. Less common ones include: epithelial downgrowth into the anterior chamber, ciliovitreal block (malignant glaucoma), the presence of degenerated red blood cells in the angle region (ghost cell glaucoma) and the so far little known mechanisms related to chronic inflammation. Treatment of secondary glaucoma in aphakic eyes includes a wide range of methods which should be used considering the possible pathomechanism in advance. The success of trabeculectomy is not satisfactory. It seems that glaucoma drainage devices can be used with therapeutic effect. There is still a need for more research to expand our knowledge on this topic.